Isolated Ventricular Noncompaction Syndrome in a Nigerian Male: Case Report and Review of the Literature. (15th July 2010) - Bhattacharya, Indrani S.; Dweck, Marc; Gardner, Andrew; Jones, Mark; Francis, Mark
Abstract : Isolated ventricular non-compaction cardiomyopathy (IVNC) is a rare, morphologically distinct primary genetic cardiomyopathy, which is now gaining prominence as an important differential diagnosis in patients presenting with cardiac failure. We describe a case report of a Nigerian male with facial dysmorphism presenting with cardiac failure. This is followed by a review of the literature with focus on the diagnosis of this condition, which may be difficult especially in non-Caucasian populations.